Physical Fitness Status of Male, and Female Non-Athlete in Nigeria - Surajudeen Tosho Bakinde (Universitas Pendidikan Indonesia (UPI), 2022)
The study specifically investigated cardiorespiratory endurance, muscular strength, flexibility, and body composition of male and female non-athletes in Nigeria concerning their physical fitness status. A descriptive research design of survey type was used. The population comprised all 100 non-athletes. Purposive and simple random sampling techniques were used. We structured a questionnaire validated by three experts. A reliability coefficient of 0.70 was obtained using Pearson Product Moment Correlation. Data collection was conducted by the researcher, and two trained research assistants. The four hypotheses were tested using inferential statistics of Chi-square at 0.05 alpha level. The findings of this study showed a significant influence of cardiorespiratory endurance as well as physical fitness of male and female non-athletes. Also, there was a significant influence on muscular strength and physical fitness, flexibility and physical fitness status, as well as body composition and physical fitness status of male and female non-athletes. Non-athlete students should engage in physical activities to promote cardiorespiratory endurance during any exercise. Non-athlete students should engage in regular training with weights or using the weight of the body for resistance during calisthenics exercises to promote muscular strength in them.